KONTRIBUSI PAJAK DAERAH DAN RETRIBUSI DAERAH TERHADAP PAD DAN APBD (Studi Kasus Pada Pemerintah Daerah Kabupaten Kendal) (Students' Journal of Accounting and Banking, 2012)
The purpose of this study to determine the contribution of local taxes and levies on revenue (PAD) and the Revenue and Expenditure (Budget), the magnitude of the growth rate of local taxes and levies, and the effectiveness of local taxes and levies. This research is a descriptive study. This research is a field study conducted in Kendal Regional Government during the period 2008- 2011..The population in this study is data local taxes and levies contained in the Revenue Department of Finance and Asset Management District and Kendal In this study researchers used a data sample of local taxes and levies in 2008-2011 found on the Department of Finance and Asset Management Revenue Regional Kendal. The analysis tools such as the level of growth, contribution and effectiveness.The results showed that the local tax contribution to the budget for the period 2008-2011 at an average of 2.65% per year. Contribution to the local tax revenue over the period 2008-2011 at an average of 27.58% per year. The effectiveness of local taxes averaged 120.89%, this means that the Government Dareh Kendal has been very effective in the area of tax collection. Meanwhile, the growth rate increased levies. Contribution retribution against budget during the periods of 2008-2011 reached an average of 2.95% per year. Contribution to revenue levies during the period 2008-2011 at an average of 30.76%. Effectiveness levies averaged101.23%, this means Kendal Regional Government has been quite effective in collecting levies.Keywords: Local Taxes, Levies, Revenue, Revenue and Expenditure Budget